Performance of colloidal CdS sensitized solar cells with ZnO nanorods/nanoparticles - Roy, Anurag; Das, Partha Pratim; Tathavadekar, Mukta; Das, Sumita; Devi, Parukuttyamma Sujatha (Beilstein Journal of Nanotechnology, 2017)
As an alternative photosensitizer in dye-sensitized solar cells, bovine serum albumin (BSA) (a nonhazardous protein) was used in the synthesis of colloidal CdS nanoparticles (NPs). This system has been employed to replace the commonly used N719 dye molecule. Various nanostructured forms of ZnO, namely, nanorod and nanoparticle-based photoanodes, have been sensitized with colloidal CdS NPs to evaluate their effective performance towards quantum dot sensitized solar cells (QDSSCs). A polysulphide (S-x(2-))-based electrolyte and CuxS counter electrode were used for cell fabrication and testing. An interesting improvement in the performance of the device by imposing nanorods as a scattering layer on a particle layer has been observed. As a consequence, a maximum conversion efficiency of 1.06% with an open-circuit voltage (V-OC) of 0.67 V was achieved for the ZnO nanorod/nanoparticle assembled structure. The introduction of ZnO nanorods over the nanoparticle led to a significant enhancement of the overall efficiency compared to the corresponding bare nanoparticles.

Hydrothermally synthesized fluorescent Zn2SnO4 nanoparticles for dye sensitized solar cells - Das, Partha Pratim; Roy, Anurag; Agarkar, Shruti; Devi, Parukuttyamma Sujatha (Dyes and Pigments, 2018)
In this work, we have investigated the interaction of hydrothermally synthesized Zn2SnO4 (ZTO) nanoparticles (NPs) with two different commercial photo sensitizers such as N719 and N3 dye molecules and studied their performance in dye sensitized solar cells (DSSC). Interestingly, the ZTO NPs exhibited band edge emission in the mid UVA region and as a result possibility of enhanced light harvesting in the terminal UVA region was anticipated in the device due to the efficient energy transfer observed in case of the sensitizer N719 than N3. The dye sensitization property has been found to be higher for the N3 dye molecules than the N719 dye molecules as based on the time dependent dye loading study. The devices fabricated with ZTO-N719 exhibited improved photovoltaic performance compared to the ZTO-N3 based devices exhibiting an overall conversion efficiency of 2.56% by the former compared to the later (1.90%) under 1SUN 1.5AM illumination and sensitization for 12 h.

Interface-centric strategies in kesterite solar cells: addressing challenges, solutions, and future directions for efficient solar-harvesting technologies - Jagadish, Kusuma; Rahane, Ganesh K.; Kumar, Boddeda Sai; Borkar, Durgesh R.; Chordiya, Kalyani; Kavanagh, Sean R.; Roy, Anurag; Debnath, Tushar; Kolekar, Sadhu; Kahaly, Mousumi Upadhyay; Mali, Sawanta S.; Pal, Shovon; et al. (SMALL, 2024)
Keywords: band engineering; Defects; interface loss mechanism; kesterites; recombination control; solar energy

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.